The Influence of Price, Place, and Promotion on Guests' Repurchase Intention at Pangeran City Hotel - Muhammad Aidil Irsan; Azmen Kahar (Journal of Multidimensional Management, 2026)
This study aims to analyze the influence of price, place, and promotion on guests' repurchase intention at Pangeran City Hotel, Padang. The research was motivated by occupancy-rate fluctuations and guest complaints concerning the mismatch between room rates and facilities, limited parking availability, and underperforming promotional activities. A quantitative causal-associative design was employed. Data were collected through a structured questionnaire distributed to 100 respondents who had checked out from Pangeran City Hotel, selected using purposive sampling. The instrument was measured using a five-point Likert scale and tested for validity and reliability prior to data collection. Data were analyzed using multiple linear regression in IBM SPSS Statistics version 26 after fulfilling the classical assumption tests of normality, heteroscedasticity, and multicollinearity. The results show that price (β = 0.363; p = 0.011) and place (β = 0.422; p = 0.001) have positive and significant effects on repurchase intention, while promotion (β = 0.245; p = 0.119) has a positive but insignificant effect. Place is the most dominant predictor. Simultaneously, the three variables explain 63.3% of the variance in repurchase intention. The findings imply that hotel management should align room prices with delivered facilities, sustain location-based service advantages, and redesign promotional strategies to be more relevant and attractive to repeat guests.